Frontispiece: Mass Determination of Entire Amyloid Fibrils by Using Mass Spectrometry. Issue 7 (3rd February 2016) - Doussineau, Tristan; Mathevon, Carole; Altamura, Lucie; Vendrely, Charlotte; Dugourd, Philippe; Forge, Vincent; Antoine, Rodolphe
Abstract : Proteins In their Communication onpage 2340 ff., V. Forge, R. Antoine, and co‐workers report on the use of charge‐detection mass spectrometry for the characterization of amyloid fibrils. This method can be used to monitor protein aggregation in real time.